2005
DOI: 10.1002/app.21620
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion property of novel polyimides with 1‐[3′,5′‐bis(trifluoromethyl)phenyl] pyromellitic dianhydride

Abstract: Novel polyimides were synthesized from 1-[3Ј,5Ј-bis(trifluoromethyl)phenyl] pyromellitic dianhydride (6FPPMDA) by a conventional two-step process: the preparation of poly(amic acid) followed by solution imidization via refluxing in p-chlorophenol. The diamines used for polyimide synthesis included bis(3-aminophenyl)-3,5-bis(trifluoromethyl)phenyl phosphine oxide, bis(3-aminophenyl)-4-trifluoromethylphenyl phosphine oxide, and bis(3-aminophenyl)phenyl phosphine oxide. The synthesized polyimides were designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…Compared with the previous study, which reported peel strength of 94 and 91 g/mm with PPMDAmDAPPO and 3FPPMDA-mDAPPO polyimides, 19 much higher peel strength was observed in this study (130 and 121 g/mm). This difference can be explained by the different sample geometry: Cu/polyimide samples in this study compared to the Cu/polyimide/Cu samples in the previous study.…”
Section: Adhesive Properties Of Polyimidescontrasting
confidence: 60%
See 2 more Smart Citations
“…Compared with the previous study, which reported peel strength of 94 and 91 g/mm with PPMDAmDAPPO and 3FPPMDA-mDAPPO polyimides, 19 much higher peel strength was observed in this study (130 and 121 g/mm). This difference can be explained by the different sample geometry: Cu/polyimide samples in this study compared to the Cu/polyimide/Cu samples in the previous study.…”
Section: Adhesive Properties Of Polyimidescontrasting
confidence: 60%
“…19 The Cu/polyimide samples were prepared by brush coating the polyimide solution (15 wt % in NMP) on Cu foil and drying at $ 100 C for 15 min. The process was repeated until the coating thickness reached 0.04 mm, because the polyimide layer has to be thick enough to minimize plastic deformation during testing.…”
Section: Adhesive Property Of Polyimidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the ASTM D-1876 T-peel test samples (Cu/polyimide/Cu) of PPMDA-mDAPPO polyimide showed cohesive failure, despite their lower peel strength, as previously reported. 34 This can be explained by the poor flow of polyimide adhesives during thermal lamination due to their high T g , which resulted in failure occurring at the interface of two polyimide layers, despite the misleading appearance of cohesive failure.…”
Section: Adhesive Properties Of Polyimidesmentioning
confidence: 98%
“…34 The modified T-peel test samples were prepared by brush coating the Cu foil with polyimide solution (15 wt % ) from the benzene ring, indicating a successful synthesis.…”
Section: Adhesive Property Of Polyimidesmentioning
confidence: 99%